Comparative Effect of Commercially Available Nanoparticles on Soil Bacterial Community and “Botrytis fabae” Caused Brown Spot: In vitro and in vivo Experiment - Sabra, Mayada A.; Alaidaroos, Bothaina A.; Jastaniah, Samyah D.; Heflish, Ahmed I.; Ghareeb, Rehab Y.; Mackled, Marwa I.; El-Saadony, Mohamed T.; Abdelsalam, Nader R.; Conte-Junior, Carlos Adam (Frontiers in Microbiology, 2022)
This current study revealed the possible effects of various levels of silver nanoparticles (AgNPs) application on plant diseases and soil microbial diversity. It investigated the comparison between the application of AgNPs and two commercial nanoproducts (Zn and FeNPs) on the rhizobacterial population and Botrytis fabae. Two experiments were conducted. The first studied the influence of 13 AgNPs concentration on soil bacterial diversity besides two other commercial nanoparticles, ZnNPs (2000 ppm) and FeNPs (2500 ppm), used for comparison and application on onion seedlings. The second experiment was designed to determine the antifungal activity of previous AgNPs concentrations (150, 200, 250, 300, 400, and 500 ppm) against B. fabae, tested using commercial fungicide as control. Results obtained from both experiments revealed the positive impact of AgNPs on the microbial community, representing a decrease in both the soil microbial biomass and the growth of brown spot disease, affecting microbial community composition, including bacteria, fungi, and biological varieties. In contrast, the two commercial products displayed lower effects compared to AgNPs. Current results clearly showed that the AgNPs strongly inhibited the plant pathogens B. fabae growth and development, decreasing the number of bacteria (cfu/ml) and reducing the rhizosphere. Using AgNPs as an antimicrobial agent in the agricultural domain is recommended.